Modest Static Pressure Suppresses Columnar Epithelial Cell Growth in Association with Cell Shape and Cytoskeletal Modifications - Hagiyama, Man; Yabuta, Norikazu; Okuzaki, Daisuke; Inoue, Takao; Takashima, Yasutoshi; Kimura, Ryuichiro; Ri, Aritoshi; Ito, Akihiko (Frontiers in Physiology, 2017)
Intraluminal pressure elevation can cause degenerative disorders, such as ileus and hydronephrosis, and the threshold is fairly low and constant, 20–30 cm H2O. We previously devised a novel two-chamber culture system subjecting cells cultured on a semipermeable membrane to increased culture medium height (water pressure up to 60 cm H2O). Here, we sought to determine how a continuous pressure load of 30 cm H2O affects proliferating epithelial cells with special interest in the link with cell morphology. We cultured several different cell lines using the low static pressure-loadable two-chamber system, and examined cell growth, cell cycle, and cell morphology. Madin–Darby canine kidney (MDCK) columnar epithelial cells were growth-suppressed in a manner dependent on static water pressure ranging from 2–50 cm H2O, without cell cycle arrest at any specific phase. Two other types of columnar epithelial cells exhibited similar phenotypes. By contrast, spherical epithelial and mesenchymal cells were not growth-suppressed, even at 50 cm H2O. Phalloidin staining revealed that 50 cm H2O pressure load vertically flattened and laterally widened columnar epithelial cells and made actin fiber distribution sparse, without affecting total phalloidin intensity per cell. When the mucosal protectant irsogladine maleate (100 nM) was added to 50-cm-high culture medium, MDCK cells were reduced in volume and their doubling time shortened. Cell proliferation and morphology are known to be regulated by the Hippo signaling pathway. A pressure load of 50 cm H2O enhanced serine-127 phosphorylation and cytoplasmic retention of YAP, the major constituent of this pathway, suggesting that Hippo pathway was involved in the pressure-induced cell growth suppression. RNA sequencing of MDCK cells showed that a 50 cm H2O pressure load upregulated keratin 14, an intermediate filament, 12-fold. This upregulation was confirmed at the protein level by immunofluorescence, suggesting a role in cytoskeletal reinforcement. These results provide evidence that cell morphology and the cytoskeleton are closely linked to cell growth. Pathological intraluminal pressure elevation may cause mucosal degeneration by acting directly on this linkage and the Hippo pathway.